2016
DOI: 10.20892/j.issn.2095-3941.2016.0063
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of intrahepatic cholangiocarcinoma: a retrospective study of 104 cases

Abstract: Objective: To explore the clinicopathological features, surgical treatment techniques, and prognostic risk factors of intrahepatic cholangiocarcinoma (ICC).Methods: A total of 104 ICC cases were collected from January 2008 to December 2013 at Tianjin Medical University Cancer Institute and Hospital and divided into the hepatic hilum lymphadenectomy (HLL, 21 cases), extended hepatic hilum lymphadenectomy (EHLL, 12 cases), and non-lymphadenectomy (NL, 71 cases) groups. The clinical data of the patients were retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Previous studies [ 29 , 30 ] showed that CA242 could improve the accuracy of ICC diagnosis. Meanwhile, only one literature from the authors' center [ 24 ] found that ferritin was an independent predictor of OS in ICC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [ 29 , 30 ] showed that CA242 could improve the accuracy of ICC diagnosis. Meanwhile, only one literature from the authors' center [ 24 ] found that ferritin was an independent predictor of OS in ICC.…”
Section: Discussionmentioning
confidence: 99%
“…CEA is independent of serum bilirubin levels, and it may have a predictive value for surgical resection rates. Two studies reported that ferritin may serve as a risk factor for postoperative survival of patients with ICC [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…AGR 0.5 after hepatectomy in HCC patients has been reported as an independent prognostic factor [33]. Intrahepatic cholangiocarcinoma (ICC) elevation of serum ferritin has been found to be associated with poor prognosis [37]. Vohra et al found that serum ferritin and transferrin ratio has been shown to be a prognostic biomarker in HCC patients [38].…”
Section: Discussionmentioning
confidence: 99%
“… 35 , 36 However, routine lymph node dissection did not improve long-term survival. 37 , 38 We did not perform routine lymph node dissection unless lymph node metastasis was suspected intraoperatively. Those with histologically proved lymph node metastases were excluded to simplify the initial tumor stage in this study.…”
Section: Discussionmentioning
confidence: 99%